Laney P' Chart Effectiveness in Quality Control of Cigar Production - Indraswari, Salsabila Putri; Suprihanti, Antik (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
AbstractThis study aimed to evaluate the effectiveness of Laney p' chart in overcoming the limitations of conventional p-chart in cigar quality control, especially in handling overdispersion of production data. Overdispersion often occurs in agricultural processes with large sample sizes, resulting in narrow control limits and false alarms. The study was conducted at PT Taru Martani, using cigar quality data from three main production units from August 2021 to July 2022. A quantitative descriptive approach was used to analyze the proportion of product defects. Initial analysis with conventional p-chart showed that 29,140 units in the Cocoon Unit, 23,602 units in the Rolling Unit, and 5,987 units in the Dry Cigar Unit were out of control due to overdispersion. After the Laney p' chart application, the control limits were expanded to 234.7%, significantly reducing false alarms and increasing sensitivity to actual variations in the data. The analysis showed that Laney p' chart was more effective in identifying relevant process variations. The process in the Dry Cigar Unit continued to show instability, likely due to humidity and raw material quality fluctuations. These findings highlight the importance of environmental control and raw material stability in maintaining product quality. This study provided practical contributions to the quality control of high-value agricultural products. It is recommended that further studies explore the integration of other statistical methods and study deeply the relationship between external factors and product quality.Keywords: Agricultural products, cigars, Laney p' chart, overdispersion, quality control AbstrakPenelitian ini bertujuan untuk mengevaluasi efektivitas Laney p' chart dalam mengatasi keterbatasan p-chart konvensional pada pengendalian mutu cerutu, khususnya dalam menangani overdispersi data produksi. Overdispersi sering kali muncul dalam proses agrikultur dengan ukuran sampel besar, menghasilkan batas kendali yang sempit dan alarm palsu. Studi dilakukan di PT Taru Martani, menggunakan data mutu cerutu dari tiga unit produksi utama selama Agustus 2021 hingga Juli 2022. Pendekatan deskriptif kuantitatif digunakan untuk menganalisis proporsi kecacatan produk. Analisis awal dengan p-chart konvensional menunjukkan bahwa 29.140 unit di Unit Kepompong, 23.602 unit di Unit Pelintingan, dan 5.987 unit di Unit Cerutu Kering berada di luar kendali akibat overdispersi. Setelah penerapan Laney p' chart, batas kendali diperluas hingga 234,7%, mengurangi alarm palsu secara signifikan dan meningkatkan sensitivitas terhadap variasi nyata dalam data. Hasil analisis menunjukkan Laney p' chart lebih efektif dalam mengidentifikasi variasi proses yang relevan. Proses di Unit Cerutu Kering, misalnya, tetap menunjukkan ketidakstabilan, kemungkinan akibat fluktuasi kelembaban dan kualitas bahan baku. Temuan ini menyoroti pentingnya pengendalian lingkungan dan stabilitas bahan baku dalam menjaga mutu produk. Penelitian ini memberikan kontribusi praktis dalam pengendalian mutu produk agrikultur bernilai tinggi. Disarankan agar studi lanjutan mengeksplorasi integrasi metode statistik lain dan mempelajari hubungan lebih dalam antara faktor eksternal dengan mutu produk.Kata kunci: Cerutu, Laney p' chart, overdispersi, pengendalian mutu, produk agrikultur